Evaluating The Implementation of The Spiral Curriculum of Communicable Disease in Undergraduate Program of Medicine - Khoiriyah, Umatul (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: Non-communicable diseases, including cardiovascular disease, cancer, and chronic lung disease, are responsible for around 74% of all deaths worldwide. Medical doctors should have the competencies to manage this disease. For this reason, all medical schools should include this disease in the curriculum. The Faculty of Medicine has included non-communicable diseases as one of the main parts of the curriculum. FM UII designed the curriculum spirally, which means there is repetition in a curriculum but with increasing levels of complexity. Method: This study was a quantitative study using observational design. The subject of the study was last year's students in the undergraduate program at FM UII (n=156). Cohort data was collected through students' written examination scores in cardiovascular course (1.4), hemodynamic problem (2.3) studying the pathophysiology of cardiovascular disease and disease in adults (3.5), which learn the management of cardiovascular disease. The correlation of the examination score of each course was analyzed using Pearson correlation. Results: The mean of the second-year course (hemodynamic problem) is the highest, followed by the cardiovascular course, and the last is the disease in the adult course. There is a significant correlation among the score of each course (p=0.000, with range from 0.6 to 0.7). Discussion: Anatomy and physiology of the cardiovascular system is the basis for students to learn the pathophysiology, diagnosis, and management of cardiovascular disease. Moreover, the student's knowledge of the pathophysiology of the cardiovascular problem also relates to students' knowledge of the diagnosis and management of human disease. Conclusion: The implementation of non-communicable disease in the curriculum of the undergraduate program of FM UII shows that the curriculum has been designed well for its spiral. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S37